친환경농업 시스템 구축을 위한 지역단위 물질균형 분석 - 김창길 (KREI, 2003)
The material balance approach provides a method for assessing nutrient surpluses of specific villages or regions, and hence their environmental loads. This approach makes it possible to assess the effect of agri-environmental policy measures on nutrient runoff. The objectives of this paper are to present a nutrient balance model relating to Yangpyeong County, and to discuss the problem of using it for assessing environmental pressure from agricultural production activities in order to give an overview of the agri-environmental policy programs. This paper reviews the conceptual framework for the material balance approach using the Condition-State-Plan (C-S-P) system and formulates a regionally based material balance model using the nutrient balance equation. The regional material balance model based on inflow and outflow of nutrients in Yangpyeong County is set up as an illustrative example. Also included are policy implications for activating integrated nutrient management, a multi-level approach involving all stakeholder, and suggestions for further study for increasing the accuracy of a material balance model.
Keywords: 물질균형; 농업생태계; 자정작용; 열역학 제1법칙; 열역학 제2법칙; 엔트로피; Material Balance; Agro-ecosystem; Assimilative Capacity; The 1st Law of Thermodynamics; The 2nd Law of Thermodynamics; Entropy